Pediatric Tuina for the treatment of functional dyspepsia: A systematic review and meta-analysis of randomized controlled trials - Na-Yeon Ha; Chang-Yul Keum; Jinsung Kim (Complementary Therapies in Medicine)
Background: Functional dyspepsia (FD) is the most prevalent pediatric gastrointestinal disorder, imposing a significant burden on healthcare services and often persisting into adulthood. Tuina, a traditional manual therapy, is frequently employed in the treatment of FD. This study aimed to systematically evaluate the efficacy and safety of Tuina in treating FD in children. Methods: A comprehensive search of 11 databases was conducted for randomized controlled trials (RCTs) published up to June 2022. Two independent reviewers screened the literature, extracted data, assessed the methodological quality of the RCTs using the Cochrane risk-of-bias tool, and performed meta-analysis using Review Manager software to quantify Tuina’s efficacy. Results: The review covered ten RCTs with 1336 children. Tuina, alone or with conventional therapy (CT), significantly improved efficacy rates over CT alone (relative risk (RR) = 1.16, 95 % confidence interval (CI) [1.11, 1.21], p < 0.00001). The combined Tuina group demonstrated significantly lower overall dyspeptic symptom scores (standard mean difference (SMD) = -1.18, 95 % CI [-1.46, −0.91], p < 0.00001) and shorter times to resolution of primary symptoms, including abdominal distension (mean difference (MD) = -2.08, 95 % CI [-2.35, −1.81], p < 0.00001), abdominal pain (MD = −1.54, 95 % CI [-1.92, −1.17], p < 0.00001), belching (MD = −1.11, 95 % CI [-1.44, −0.77], p < 0.00001), and anorexia (MD = −1.37, 95 % CI [-1.67, −1.07], p < 0.00001). Additionally, the recurrence rate following treatment was significantly lower (RR = 0.32, 95 % CI [0.14, 0.72], p = 0.006). The levels of serum motilin (MD = 22.93, 95 % CI [13.56, 32.30], p < 0.00001) and urinary excretion of D-xylose (MD = 3.11, 95 % CI [0.31, 5.92], p = 0.03) were also elevated. There were no significant differences between the combined Tuina and CT groups regarding the four individual dyspeptic symptoms or neuropeptide Y levels. No adverse events were reported in the Tuina group. Conclusion: This systematic review collectively suggest that Tuina effectively and safely improves clinical symptoms in children with FD. However, addressing identified methodological weaknesses is crucial for future studies to ensure robust evidence.